2009
DOI: 10.1088/0067-0049/186/1/94
|View full text |Cite
|
Sign up to set email alerts
|

An Extremely Deep, Wide-Field Near-Infrared Survey: Bright Galaxy Counts and Local Large Scale Structure

Abstract: We present a deep, wide-field near-infrared (NIR) survey over five widely separated fields at high Galactic latitude covering a total of ∼ 3 deg 2 in J, H, and K s . The deepest areas of the data (∼ 0.25 deg 2 ) extend to a 5 σ limiting magnitude of JHK s > 24 in the AB magnitude system. Although depth and area vary from field to field, the overall depth and large area of this dataset make it one of the deepest wide-field NIR imaging surveys to date. This paper discusses the observations, data reduction, and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 57 publications
5
29
0
Order By: Relevance
“…Similar positive deviations have also been reported by other studies (Sandage et al 1972;Afshordi et al 2004). As noted by Keenan et al (2010), a positive deviation with respect to the homogeneous β = 0.6 value also suggests that the local Universe could be under-dense on scales of a few hundred Mpc. This underdensity could have an impact in explaining the differences between local measurements of the expansion rate and those derived from CMB observations (Keenan et al 2012).…”
Section: Number Densitysupporting
confidence: 87%
“…Similar positive deviations have also been reported by other studies (Sandage et al 1972;Afshordi et al 2004). As noted by Keenan et al (2010), a positive deviation with respect to the homogeneous β = 0.6 value also suggests that the local Universe could be under-dense on scales of a few hundred Mpc. This underdensity could have an impact in explaining the differences between local measurements of the expansion rate and those derived from CMB observations (Keenan et al 2012).…”
Section: Number Densitysupporting
confidence: 87%
“…The existence of a large local void would be consistent with studies of near-infrared (NIR) galaxy counts that have found the local space density of galaxies may be low by 25%-50% compared with the density at distances of ∼300 h −1 Mpc or z ∼ 0.1 (Keenan et al 2010b;Busswell et al 2004;Frith et al 2003Frith et al , 2005Huang et al 1997). Galaxy counts in the NIR at low redshifts are primarily sampling L ∼ L * or brighter galaxies (Barro et al 2009).…”
Section: Introductionsupporting
confidence: 82%
“…More recently Keenan et al (2010Keenan et al ( , 2012 and Keenan, Barger & Cowie (2013) have compared galaxy counts and luminosity density at high and low redshift and reported evidence for a 300 Mpc void with a 50 per cent underdensity. Alternative probes than Kband galaxy surveys have also been used to study this hypothesis.…”
Section: Introductionmentioning
confidence: 99%